2015
DOI: 10.1177/1464420715586020
|View full text |Cite
|
Sign up to set email alerts
|

Fluid handling and fabric handle profiles of hydroentangled greige cotton and spunbond polypropylene nonwoven topsheets

Abstract: Wettable nonwoven topsheets are traditionally spunbond polypropylene nonwoven fabrics. The fluid handling performance of hydroentangled greige cotton nonwovens was studied to determine their suitability for topsheet applications based upon analysis of fluid rewet, strikethrough, and acquisition properties; and the relative contributions of nonwoven cotton's cellulosic and wax components to hydrophobic and hydrophilic fluid transport properties are addressed. It was observed that mechanically cleaned greige cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…In this regard, it is notable that materials with contact angle measurements from ninety degrees to one hundred and twenty degrees have a high degree of hydrophobicity. As demonstrated previously, fabrics having at least 30 percent of greige cotton and 20 percent of polypropylene give rise to contact angles that indicate hydrophobicity [35,36]. This is seen to some extent in this study, but in fabric finishes such as ascorbic acid, the nonwoven's fibrous web porosity and the zeolite formulation application decreased the contact angle to below the threshold of hydrophobic character.…”
Section: Discussionsupporting
confidence: 79%
“…In this regard, it is notable that materials with contact angle measurements from ninety degrees to one hundred and twenty degrees have a high degree of hydrophobicity. As demonstrated previously, fabrics having at least 30 percent of greige cotton and 20 percent of polypropylene give rise to contact angles that indicate hydrophobicity [35,36]. This is seen to some extent in this study, but in fabric finishes such as ascorbic acid, the nonwoven's fibrous web porosity and the zeolite formulation application decreased the contact angle to below the threshold of hydrophobic character.…”
Section: Discussionsupporting
confidence: 79%
“…It has previously been suggested that fiber diameter and arrangement within the fabric structure contribute to the moisture wicking rate through the size of interstitial channels formed by these fibers. 41,44,[50][51][52] In our study, for both heavyweight and lightweight spunlaced fabrics, fineness showed a strong positive correlation with the top and bottom spreading speeds as well as the OMMC. In the 24-mesh samples produced at different pressures, the fiber micronaire displayed a strong negative correlation with the first runoff event.…”
Section: Discussionsupporting
confidence: 54%
“…For example, lighter weight HE fabrics may not require high tensile strength in less physically rigorous applications such as diaper, incontinence, and other hygiene components where fluid handling properties are of greater importance. 43 However, lightweight HE fabrics utilized for disposable wipes applications, disposable apparel or hospital bedding require higher tensile strength to prevent structural failure during usage. Of particular interest was the increase in tensile strength of heavyweight nonwoven fabrics produced from coarse cotton fibers.…”
Section: à0041mentioning
confidence: 99%